Using Operational Breakeven Point and Relative Solvency Ratio as Discriminant Tools to Highlight Firms’ Corporate Survival Index - Enyi , Enyi Patrick (Current Topics on Business, Economics and Finance Vol. 9, 2023)
Corporate financial management paradigms need to change because the current technologies have repeatedly shown indications of being unable to effectively handle solvency issues. The relative solvency ratio, an offshoot of the operational breakeven point, measures the solvency or liquidity status of a business in terms of the availability of working capital. The main driving force behind the operational breakeven point is the mark-up ratio(m) which maintains a trade-off relationship with the former; meaning the higher the mark-up rate, the lower the operational breakeven point and vice versa. As a more useful substitute for the current instruments for discriminant analysis and corporate financial management, the operational breakeven theory was presented. The theory has undergone extensive testing with positive results in Asia and Africa.